2013
DOI: 10.1002/adem.201200327
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Defects Contributing to the Energy Absorption in CrMnNi TRIP Steels

Abstract: Freiberg for the hot rolled TRIP steel samples. For the metallographic sample preparation we would like to thank Mrs. Dipl.-Ing. A. Mueller, Mrs. K. Becker; for the conventional preparation of TEM samples and the FIB preparation of TEM samples on Infineon, Dresden we would like to thank Mrs. Dipl.-Ing. A. Leuteritz.Microstructure defects control the TRIP effect and/or the TWIP effect and contribute significantly to the absorption of deformation energy in plastically deformed austenitic CrMnNi steels. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…(ii) In certain cases, only diffuse stacking fault arrangements are formed by deformation in TWIP/TRIP steels, as observed by Borisova et al [48]. These should not be treated as compact aggregates of ε-martensite and would not be identified as such by EBSD [48,49]. (iii) According to the reasoning provided in Ref.…”
Section: Mechanical Characterizationmentioning
confidence: 93%
“…(ii) In certain cases, only diffuse stacking fault arrangements are formed by deformation in TWIP/TRIP steels, as observed by Borisova et al [48]. These should not be treated as compact aggregates of ε-martensite and would not be identified as such by EBSD [48,49]. (iii) According to the reasoning provided in Ref.…”
Section: Mechanical Characterizationmentioning
confidence: 93%
“…A sigmoidal shape of the stress-strain curve is a good indicator for the martensitic phase transformation, visible in the electron backscattering diffraction (EBSD) maps in Figure 1b and c. During tensile deformation, deformation bands (yellow) with a hexagonally indexed lattice structure and a thickness of a few micrometres or less develop. In references [19][20][21], it was shown that the hexagonally indexed regions (usually called ε-martensite) are formed by a high density of stacking faults. These bands and their intersection points are nucleation sites for α'-martensite (blue) with a size in the order of few μm or less [19,22] as shown by the orientation map in Figure 1c.…”
Section: Introductionmentioning
confidence: 99%
“…In references [19][20][21], it was shown that the hexagonally indexed regions (usually called ε-martensite) are formed by a high density of stacking faults. These bands and their intersection points are nucleation sites for α'-martensite (blue) with a size in the order of few μm or less [19,22] as shown by the orientation map in Figure 1c.…”
Section: Introductionmentioning
confidence: 99%
“…[21] Because of a high density of SFs in the deformation bands of the austenite, hexagonal areas are formed, which appear as hcp phase (e-martensite) in X-ray diffraction experiments or in TEM and EBSD investigations. [22,23] Therefore, a continuous phase transformation sequence c fi e fi a¢ is often found in this type of steels. Via the c fi e fi a¢ transformation route, the nucleation of the a¢-martensite needs much less activation energy than the c fi a¢ route.…”
Section: Introductionmentioning
confidence: 99%